PENGARUH STRATEGIC LEADERSHIP, CORPORATE CULTURE, COMMITMENT MANAGEMENT, INNOVATION DAN COMPETITIVE ADVANTAGE DI MODERASI CHANGE MANAGEMENT TERHADAP CORPORATE PERFORMANCE PT LEKOM MARAS - Suprianto, Edy Suprianto; Derriawan; Zulkifli (SEKOLAH PASCASARJANA PRESS, 2021)
he purpose of this study was to determine the effect of strategic leadership, coporate culture, commitment management, change management moderated competitive advantage on coporate performance of PT. Lekom Maras. The sample method in this study uses probability sampling, where each member of the population has the opportunity or or has the same opportunity to be used as a sample. The sample in this study were employees of PT Lekom Maras who are in the strategy and business development division, there are General Managers, managers and team leaders. The number of samples is 140 people. The statistical method used in this research is Structural Equation Modeling (SEM) which is operated through the SmartPLS3 program. This research shows that the variables of Leadership Strategy, Innovation, Commitment Management have a positive and significant effect on competitive advantage, competitive advantage has a positive and significant effect on corporate performance. Meanwhile, Corporate Culture has no significant effect on Competitive advantage and Change management as a moderating variable that moderates Competitive advantage does not have a significant effect on corporate performance.